Human Resource Development Strategy : Digitalization and Artificial Intelligence in West Java Province, Indonesia - Ariesmansyah, Andre; Rosid, Abdul; Arifin, Rifqi Khairul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digitalization and artificial intelligence have brought significant changes to various sectors, both economic, social, and governmental. for the province of West Java. The challenge of developing human resources requires adaptation to technological changes. West Java Province is one of the largest provinces in Indonesia that faces various challenges related to the development of digitalization and artificial intelligence. The strategy for developing human resources in West Java Province in facing digitalization and artificial intelligence must be carried out comprehensively and involve various stakeholders.